Seasonal variations in phytoplankton abundance of Ambona lake Maharashtra - Bhoyar, V V; Tamloorkar, H L (International Multidisciplinary Research Journal, 2012)
Present investigation deals with the quantitative and qualitative information on seasonal variations of phytoplanktons on Ambona Lake in Umarkhed Taluka Yavatmal district. Phytoplankton’s play an important role as food for herbivorous animals (primary production) and acts as biological indicators of water quality in pollution studies. Hence the present study was carried out on Ambona lake for a period of one year from Jun 2010 to May 2011. The samples were collected and identified using standard keys of APHA [1]. Altogether twenty one species of phytoplankton’s belonged to four class were identified. Out of the 11 species belonged to chlorophyceare, and 5 species belonged to Bacillarophyceae, 4 species belonged to cyanophyceae, and 1 species belonged to Euglenophyceae.